Metaverse for Health: Future Opportunities, Challenges, and Recommendations - Tuba, Syahrul; Arief , Ilham; Sudasman, Fuad Hilmi; Bakhar, Muhamad; Ernawati, Kholis; Thomason, Jane (Universitas Pahlawan Tuanku Tambusai, 2024)
Metaverse is a concept that refers to a virtual world that is globally integrated and can be accessed by many people from various places. This research aims to further discuss the metaverse for health and its challenges. The method used by researchers in this study is the literature research method. The benefits of metaverse technology for health include health education, health therapy, health remote monitoring, health research, telemedicine, health rehabilitation, and health specialist consultations. The challenges that must be faced by the metaverse in health include relatively new technology, high-quality standards, accessibility, regulation, health professionals (doctors, nurses, etc.) must be trained, interoperability, adaptation, a large investment of funds, clinical studies, and so on.